RARE-46. A THIRTEEN YEAR PATIENT JOURNEY OF INFANT GIANT CLIVAL CHORDOMA: CASE REPORT AND LITERATURE REVIEW. (4th December 2020) - Apps, John; Neumann, Eloise; Afshari, Fardad; Solanki, Guirish; English, Martin
Abstract: In 2006 we reported the youngest case of a large clival chordoma, a 15-week old baby, the second case to present without skull base involvement and the fourth case of chordoma in a patient with tuberous sclerosis. This unusually rare case (surgically un-resect able) underwent endoscopic skull-base diagnostic biopsy and a novel chemotherapy regime that aimed to control his disease[i]. Initial tumour control was achieved with chemotherapy (Ifosfamide, doxorubicin with dexrazonane, intrathecal hydrocortisone, methotrexate, cytarabine). Carboplatin and etoposide were later given for a further year. Following this, Sirolimus and imatinib were used for another twelve months due to primary tumour regrowth and three new skull-vault lesions. Sirolimus alone was continued for an additional year, but stopped due to optic neuritis. Imatinib was given until further progression two years later, leading to a change to everolimus. Surgery for the ventral foramen magnum was performed a year later. The patient received further surgery and radiotherapy for tumour recurrence. Sadly the tumour metastasised and he succumbed at age 13. Chordomas are aggressive and recur frequently. Complete primary resection followed by radiotherapy/proton beam therapy offers the best chance of cure but is not an option in infants with giant lesions, as in our case. We inform on alternative targeted treatment strategies and review the literature on these rare lesions. [i] Kambogiorgas D, St George EJ, Chapman S, English M, Solanki G: Infantile Clivus chordoma without clivus involvement: Case report and review of the literature, Childs Nerv System (2006) 22:1369–1374